Role of platelet to lymphocyte ratio in assessing prognosis in acute pancreatitis - Reddy, Challapalli Srikanth; Karimaddela, Keerthinmayee; Theja, Peddavenkatagari; Prakash, Gandikota Venkata; Kumar, Pustela Mahesh (International Surgery Journal, 2019)
Background: Acute pancreatitis is a common condition associated with morbidity and mortality. The incidence of acute pancreatitis (AP) has been increasing worldwide. Recent advances in diagnostic and therapeutic management in acute pancreatitis (AP) remarkably decreased the mortality rate. Assessing severity of acute pancreatitis at an early stage will further decrease the mortality rate and will help to initiate appropriate treatment as early as possible to prevent mortality. Many clinical, laboratory, and radiological factors and scoring systems are used to predict severity and prognosis of AP, but none is ideal. In low resource setting, costly laboratory tests are not readily available. Platelet to lymphocyte ratio (PLR) is an easily derivable, cost effective and applicable blood test. Platelet to lymphocyte ratio (PLR) is a relatively novel inflammatory marker and can predict severity in various diseases. In this study, we evaluated the value of PLR as prognostic factor in acute pancreatitis (AP). Methods: This prospective study was conducted on 256 patients admitted to S.V.R.R.G.G. Hospital, with the diagnosis of acute pancreatitis, from April 2017 to September 2018. Patients with Acute Pancreatitis were divided into tertiles based on the values of PLR at admission, a PLR of less than 150 as 1st tertile, a PLR of 150-300 as 2nd tertile and a PLR of more than 300 as 3rd tertile. The outcomes assessed were intensive care unit (ICU) admission, length of stay (LOS) in the hospital and death. Results: According to PLR tertiles, patients in the 3rd tertile (PLR>300) had significantly more ICU admissions, 59 (71%) and longer average Length of Hospital Stay (LOS) of survivors,18+/-5 days and higher mortality, 24 (28.9%), compared with those in the 1st tertile (PLR<150). Conclusions: PLR is an easily derivable, cost effective prognostic factor which can predict the outcome of acute pancreatitis. In this study, we established that high PLR value is associated with very bad prognosis and poor outcome or death in Acute pancreatitis.